2011
DOI: 10.2478/v10019-011-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles as targeted delivery systems in oncology

Abstract: BackgroundMany different types of nanoparticles, magnetic nanoparticles being just a category among them, offer exciting opportunities for technologies at the interfaces between chemistry, physics and biology. Some magnetic nanoparticles have already been utilized in clinical practice as contrast enhancing agents for magnetic resonance imaging (MRI). However, their physicochemical properties are constantly being improved upon also for other biological applications, such as magnetically-guided delivery systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
128
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 97 publications
(147 reference statements)
1
128
0
1
Order By: Relevance
“…Positively charged particles appear to be the ones provoking a larger toxicity, although this has to be balanced against the fact that the internalization is favored by even small amounts of positive surface charge. iii) The hydrophilic/hydrophobic balance of the particles is also an essential characteristic: decreasing hydrophilicity increases in turn the capacity of the opsonins to adsorb on the particles, and hence makes it easier the NP recognition by the phagocytic cells (Prijic & Sersa, 2011). iv) Finally, the purity is as well an issue to take care of: biocompatibility can be significantly altered by the leaching of any impurities of the particles (and this includes some stabilizers, as well).…”
Section: Minimizing Toxicitymentioning
confidence: 99%
“…Positively charged particles appear to be the ones provoking a larger toxicity, although this has to be balanced against the fact that the internalization is favored by even small amounts of positive surface charge. iii) The hydrophilic/hydrophobic balance of the particles is also an essential characteristic: decreasing hydrophilicity increases in turn the capacity of the opsonins to adsorb on the particles, and hence makes it easier the NP recognition by the phagocytic cells (Prijic & Sersa, 2011). iv) Finally, the purity is as well an issue to take care of: biocompatibility can be significantly altered by the leaching of any impurities of the particles (and this includes some stabilizers, as well).…”
Section: Minimizing Toxicitymentioning
confidence: 99%
“…9,10 The physicochemical properties of magnetic nanoparticles, such as Ni, are constantly being improved for other biological applications, which includes magnetically-guided delivery systems for different therapeutics. 11 An in vitro study has also shown that functionalized Ni nanoparticles capped with positively charged tetraheptylammonium can efficiently enhance the permeation and uptake of quercetin into hepatocellular carcinoma cells (SMMC-7721), implying that Ni nanoparticles have potential for cancer biomedical and chemotherapeutic applications. 12 Other groups have also investigated the use of Ni nanoparticles for chemotherapeutic applications, such as the accumulation of the anticancer drug daunorubicin in leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic targeting has the advantage of not requiring complex chemical modification of targeting ligands on the surface of nanocarriers when compared with conventional tumor targeting. Exploiting a magnetic field as a driving force represents a noninvasive therapeutic approach [10,11].…”
Section: Introductionmentioning
confidence: 99%